Penguatan Manajemen Bisnis untuk Meningkatkan Daya Saing UMKM Gerai Puan Hayati - Diah Ayu Mawarti; Wawan Wibisono; Sony Junaedi; Andhika Nanda Perdhana (Universitas 17 Agustus 1945 Semarang, 2026)
This article discusses the strengthening of business management at Gerai Puan Hayati, an MSME in Central Java, through participatory mentoring. The partner faced problems including disorganised financial records, ad-hoc business planning, inconsistent branding, and limited use of digital media for promotion and market expansion. The programme was carried out through observation, interviews, focus group discussions, training, guided practice, and mentoring. The materials covered bookkeeping, cash flow management, business strategy, service enhancement, digital marketing, and mapping local cultural values as product strengths. Evaluation was conducted qualitatively by comparing the partner’s condition before and after the activities, supported by field notes and reflection. The results showed improved business administration, better understanding of cost and revenue separation, more planned use of digital media, and confidence in developing product innovation and marketing networks. This initiative also strengthened women’s participation, motivation, and awareness that local culture can serve as a sustainable competitive resource for MSMEs.